Paroxysmal Amnesia Attacks due to Hashimoto’s Encephalopathy - Pelin Nar Senol; Aylin Bican Demir; Ibrahim Bora; Mustafa Bakar (Case Reports in Medicine)
Hashimoto’s encephalopathy is a rare disease which is thought to be autoimmune and steroid responsive. The syndrome is characterized by cognitive impairment, encephalopathy, psychiatric symptoms, and seizures associated with increased level of anti-thyroid antibodies. The exact pathophysiology underlying cerebral involvement is still lesser known. Although symptoms suggest a nonlesional encephalopathy in most of the cases, sometimes the clinical appearance can be subtle and may not respond to immunosuppressants or immunomodulatory agents. Here we report a case who presented with drowsiness and amnestic complaints associated with paroxysmal electroencephalography (EEG) abnormalities which could be treated only with an antiepileptic drug.